IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN MENGGUNAKAN LKS UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS X IPA 1 MATA PELAJARAN PENDIDIKAN AGAMA ISLAM : Umi Muslihah - Umi Muslihah (LPPM STAI Darussalam Lampung, 2022)
Abstract During PAIBP learning, students were less than optimal in discussing, only certain children were active so that student learning activities were less than optimal. This study aims to improve the activities and learning outcomes of PAIBP students through the application of the STAD method using LKS, interviews, and evaluation of student learning outcomes. This research is a classroom action research (CAR) which consists of three cycles. The data collection technique used in this study is in the form of observational data from student activities during the learning process and the application of the STAD method. The results showed an increase from each cycle. This is evident from the results of student activity observation sheets which continue to increase in each cycle. This means that the application of the STAD cooperative method using LKS can improve student PAIBP learning outcomes, this can be seen from the lowest average percentage of PAIBP student learning outcomes during the pre-cycle of 36%, in the first cycle of 65.63% of 32 students , while in the second cycle of 84,38% of 32 students and in the third cycle of 86.50% of 32 students, so most of the students have completed. Meanwhile, the increase in student PAIBP learning outcomes from cycle I to cycle II was 18.75% and the increase in student PAIBP learning outcomes from cycle II to cycle III was 2.12%. So, based on the results of this study, it can be concluded that the application of the STAD method using LKS can increase the activities and learning outcomes of PAIBP students in class X IPA 1 at SMA Negeri 1 Way Jepara, East Lampung.